Incentive-Driven Information Dissemination in Two-Tier Supply Chains - Jiang, Li; Hao, Zhongyuan (Manufacturing and Service Operations Management, 2016)
We investigate information flow in two-tier supply chains, where retailers order from suppliers and sell in a market with uncertain demand. The retailers each have access to a demand signal and can exchange signals (horizontal information sharing). The suppliers can offer the retailers differential payments to gain access to their signals (vertical information acquisition). We demonstrate that retailer competition is a necessary condition to sustain information flow, whereas supplier competition precludes vertical information acquisition. Facing horizontal competition, the retailers can have an incentive to exchange signals if competition is less intense; and this incentive is stronger when they order from independent suppliers than when they order from a monopolist supplier. In the setting where two retailers order from a monopolist supplier, once the retailers exchange signals, the supplier will acquire signals from them both; otherwise, it will have an incentive to acquire signals if the signals are sufficiently correlated. It can be incentive compatible for horizontal information sharing and vertical information acquisition to coexist so that the retailers’ signals are available to all parties. Under this circumstance, the supplier will profit from information flow and the retailers can earn profit gains as well, whereas the consumers will be worse off.